Effect of Phosphorus application with and without farmyard manure on rainfed maize (Zea mays) - wheat (Triticum aestivum) - maize sequence - SURI, V K; PURI, U K (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted in low-hill submontane zone of Himachal Pradesh during 1990-91 to evaluate the direct, residual and cumulative effects of farmyard manure and phosphorus application in maize (Zea mays L.) wheat (Triticum aestivum L. emend. Fiori & Paol.) - maize sequence. Farmyard manure and P showed significant direct and residual effects on the 3 sequential crops. Farmyard manure applied during the rainy season 1990 increased the maize-grain .yield by 837 kg/ha and,Ahe grain yield of the following wheat by 332 kg/ha. P @ 26 kg/ha gave 1 334 kg/ha grain yield of wheat compared with the control. The residual farmyard manure increased the grain yield of the next maize crop by 235 kg/ha. P @ 26 kg/ha to the preceding wheat increased the grain yield of second maize crop by 300 kg/ ha. A fresh P application to the second crop @ 13 kg/ha increased its grain yield by 357 kg/ha. All the interactions were found significant. Analysis of soil after harvesting the maize crop showed a significant build up of organic carbon and available P in the plots treated with P and farmyard manure.